Short-Term Outcomes of Immediate Postpartum Intrauterine Device Insertion - Sana Hafeez, Hafsa Irshad, Fareeha Usman, Aiman Yousuf, Joveria Sadaf, Sana Aara (Journal of Islamic International Medical College, 2025)
Objective: To determine the short-term outcomes of intrauterine contraceptive device insertion performed immediately after childbirth. Study Design: Descriptive case series. Place and Duration of Study: The department of Obstetrics & Gynaecology, Shahida Islam Medical and Dental College (SIMDC), Lodhran, from April 23, 2021 to October 22, 2021. Materials and Methods: One hundred and fifty women were selected by non-probability consecutive sampling. The patients requiring post-partum contraception and fulfilling selection criteria were included in the study after informed consent. Follow up was done for 3 months after insertion of IUCD and complications such as expulsion, vaginal discharge, menstrual irregularities and lost string, were recorded on a pre-designed proforma. The SPSS version 27.0 was used for data analysis. Women's age, BMI and parity were analysed as mean and standard deviation. Complications of insertion of IUCD were recorded as frequency and percentage. Chi-square test was applied to check post stratification statistical significance. The p value ≤ 0.05 was considered statistically significant. Results: The mean age of the women was 26.79 ± 4.48 years. Thirty-nine (26%) women delivered vaginally and 111 (74%) women by caesarean section. The mean body mass index of women was 26.16 ± 5.44 kg/m2. Seventeen (11.3%) females had menstrual disturbance, 24 (14.7%) had vaginal discharge, 47 (31.3%) reported with lost string and 10 (6.7%) with IUCD expulsion. Out of these reported complications, only vaginal discharge demonstrated a statistically significant association (p = 0.013). Conclusion: The postpartum IUCD insertion is safe and effective method of contraception, with minimal complications such as expulsion, vaginal discharge, menstrual irregularities and lost string, none of which are life threatening.